PHYSICAL AND MENTAL STRESS OF PROFESSIONALS OF BODYBUILDING IN FORTALEZA (BRAZIL) (Fiep Bulletin - online, 2014)
This study aims at showing an evaluation of the strong presence of physical and mental stress in professionals of bodybuilding in Fortaleza, capital city of Ceará State, in Brazil. The sample consisted of 45 bodybuilding professionals of both sexes and of different technical levels (trainees, graduate teachers). For the collection of data, a questionnaire was adopted which was based on the Inventory of Symptoms of Stress. It had questions concerning the physical wearing-out as well as some personal and professional data. The results have indicated that stress prevailed in the graduate individuals (75%). Among the individuals suffering stress, 52% of them were circumscribed in the first phase of stress (the alert phase), and generally speaking stress was manifested more significantly in the cognitive and emotional realms of the persons interviewed, with 68% of prevalence of symptoms. Relating to the physical wearing-out, 82.2% of the sample had body pains caused by work, which were predominant in the back (86.5%) and neck (56.7%) regions. The major factors observed as responsible for the development of stress were associated with work organization, since the stressed individuals worked on an average 6 hours and 25 minutes daily and had about 45 pupils a day, whereas the nonstressed ones worked 5 hours and had 33 pupils a day. It turns out that work guidelines for bodybuilding clubs should be adopted which take into consideration such organizational aspects as working hours and number of pupils per teacher. Those aspects should be viewed as aiming at the professional's welfare so that he or she can have conditions to perform his ou her job in a fair and competent way.
Keywords: stress; bodybuilding professionals; physical wearing-out